Changes in Adult Rats’ Testis structure Induced by Hypothyroidism and Alleviating Role of L-Carnitine - Awad Hegazy, Abdelmonem; Mohammad Morsy, Manal; Said Moawad, Rania; Mohammad Elsayed, Gehad (International Journal of Human Anatomy, 2019)
Background Hypothyroidism is a metabolic disorder affecting the functions of many tissues in the body including the testis. Testis is rich in the polyunsaturated fatty acids content and lacks strong intrinsic antioxidant system making it prone to such oxidative stress. L-carnitine (LC) regulates long chain fatty acids metabolism; and is considered a valuable antioxidant factor. Aim It was to evaluate the effect of hypothyroidism induced by propylthiouracil (PTU) on rats’ testes and the possible protective role of LC. Methods Forty-eight adult male albino rats were used in this work. The animals were divided into three groups with sixteen animals in each. Group 1 (Control): Animals were kept without medications. Group 2 (PTU-treated): was subjected to administration of PTU; while group 3 (PTU and LC) received both PTU and LC. By the end of the experiment “30 days”, blood samples were taken for hormonal assay; then animals were anaesthetized and sacrificed. Specimens were homogenized for biochemical analysis; epididymal content of each rat was obtained immediately for semen analysis. Testes’ specimens were harvested, prepared and examined by light microscope examination. Results Induced hypothyroidism was noticed to cause histopathological, morphometric and biochemical changes in rat’s testes. LC protected the testicular specimens against such changes; it also improved the seminal quality and quantity as well as testicular structure and biochemistry. Conclusion Hypothyroidism could result in hazards to the structure of testis. Fortunately co-administration of LC might reduce such hazards.
Keywords: Anatomy; Adult rats; Testes; Hypothyroidism; Oxidative stress; Microanatomy.